Pre–sowing Effects of Selected Botanicals and Organics on Plant Growth, Yield and Seed Yield of Sponge gourd (Luffa aegyptiaca) Seeds under Prayagraj Zone - SOUMYANETRA KHANRA; BAZIL AVINASH SINGH; BINEETA MICHAEL BARA; VAIDURYA PRATAP SAHI (Seed Research, 2024)
The current research entitled “Pre- sowing effects of selected botanicals and organics on plant growth, yield and seed yield parameters of sponge gourd (Luffa aegyptiaca) seeds var. Alok under Prayagraj zone. A field experiment was carried out at the Field Department of Genetic and Plant Breeding, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj (U.P.) during Zaid, 2024. The experiment was laid out in Randomized Block Design (RBD), replicated thrice, consisting of 11 treatments. Seed treated with T10: Poultry manure (5%) + vermicompost (10%) recorded the higher rate of Field emergence, No. of Seeds/fruit (135.67), No. of Seeds/vine (1031.07), Seed Yield/vine (33.60 g), Seed Yield/plot (168.00 g) and Seed Yield/ ha (420.00 kg). This was followed by T9: Turmeric (1%) + vermicompost (10%) while least effective was T0: Control. Hence, the pre - sowing seed treatment with Poultry manure (5%) + vermicompost (10%) @ 8 hours could be recommended for the sponge gourd cultivation.